Thixotropic slurry for pipe jacking as well as preparation method and application of thixotropic slurry

The combination of bentonite, sodium carbonate, carboxymethyl cellulose sodium, powder coal fly ash microspheres, and glass fibers in the top-pulling mud slurry addresses issues of friction, support, and flowability, resulting in a stable and efficient mud slurry for top-pulling operations.

CN120309242APending Publication Date: 2025-07-15SHANDONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510477764.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-16
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

The existing top tube thixotropic mud has shortcomings in water retention, drag reduction and fluidity, and it is difficult to adapt to construction needs under different formation conditions.

Method used

By adding fly ash microbeads, glass fibers and potassium humate, the filtration loss, support and drag reduction performance of the thixotropic mud is optimized, and a top tube thixotropic mud with high drag reduction, strong support, low water loss and fluidity are prepared.

Benefits of technology

The mud quickly fills the gap between the pipeline and soil during the construction process, reduces friction resistance, improves construction safety and formation stability, and reduces material costs and environmental impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120309242A_ABST
    Figure CN120309242A_ABST
Patent Text Reader

Abstract

The invention discloses pipe jacking thixotropic slurry as well as a preparation method and application thereof, and belongs to the technical field of pipe jacking engineering. The thixotropic slurry for the pipe jacking is prepared from the following raw materials in percentage by mass: 6 to 10 percent of bentonite, 0.2 to 1.2 percent of sodium carbonate, 0.3 to 0.7 percent of sodium carboxymethyl cellulose, 1 to 3 percent of fly ash microbeads, 0.5 to 1.5 percent of potassium humate, 0.4 to 0.8 percent of glass fibers and the balance of water. The fly ash microbead component can fill soil particle gaps in bad stratums such as a sand layer and a pebble bed and reduce the side friction resistance during pipe jacking construction, the glass fibers can be three-dimensionally distributed in the slurry to form a glass fiber network to improve the supporting strength of the slurry, and the potassium humate does not increase the water loss rate of the thixotropic slurry and also can improve the water loss rate of the thixotropic slurry. The apparent viscosity of the slurry can be reduced, so that the slurry is better pumped, and the stability of the slurry structure is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of pipe jacking engineering, and particularly relates to a pipe jacking thixotropic slurry, a preparation method thereof, and an application thereof. Background Art

[0002] Disclosing the information of this background art section is only intended to increase the understanding of the overall background of the present invention, and is not necessarily regarded as an admission or any form of implication that this information constitutes the prior art already known to those of ordinary skill in the art.

[0003] Pipe jacking technology is a technology for construction by jacking pipes without excavating the ground surface, and has the advantages of less floor area and less environmental impact. Thixotropic slurry plays a crucial role in pipe jacking projects. Thixotropic slurry has thixotropy. When it is static, it becomes a gel state. After being disturbed, the slurry will change from the gel state to a fluid state. Injecting thixotropic slurry into the over-excavated area between the cutter head and the outer pipe wall of the pipe jacking can change the dry friction between the outer wall of the pipe and the soil layer into wet friction, reduce the pipe jacking force, and ensure the safety of construction personnel and construction equipment; in sandy or pebble layers with poor formation conditions, thixotropic slurry in the undisturbed gel state can also play a role in supporting the soil body and inhibiting soil settlement.

[0004] Currently, the most widely used raw materials for thixotropic slurry are sodium-based bentonite, soda ash, and sodium carboxymethyl cellulose (CMC), but their water retention performance and drag reduction performance need to be improved. The Chinese patent with the application number 2021101190770 discloses a pipe jacking thixotropic slurry added with fly ash microspheres. In order to reduce the water loss, fly ash microspheres and xanthan gum are added, but the mud funnel viscosity is large and the fluidity is poor. During the construction process, a large grouting pressure is required, otherwise it is difficult to form a complete mud jacket. Moreover, fly ash microspheres are hollow spheres and are easily broken and lose their mechanical properties under high pressure or shear action, resulting in limited drag reduction effect. The Chinese patent with the application number 202110520803X discloses a thixotropic slurry that can shorten the mud preparation time, but the prepared mud has poor filtration loss, and the added polyurea and lauric acid have poor chemical stability and are difficult to adapt to different construction environments. The Chinese patent with the application number 2023110118988 discloses a foam thixotropic slurry for pipe jacking drag reduction, which adds triethanolamine, water glass, and concentrated plant protein foaming agent. Its raw material cost is relatively high, the solidified product of water glass is easily deliquescent, introducing too many bubbles in the slurry will reduce the slurry density and compressive capacity, and the generated foam has a long defoaming time, prolonging the construction time.

[0005] Therefore, how to obtain a pipe jacking thixotropic slurry with high drag reduction, strong support, low water loss, and excellent fluidity has become an urgent problem to be solved by those skilled in the art. Summary of the Invention

[0006] To address the deficiencies of the prior art, the objective of the present invention is to provide a pipe-jacking thixotropic slurry, its preparation method, and application. By adding three components, namely fly ash microspheres, glass fibers, and potassium humate, it is possible to optimize the filtration performance, support performance, and drag reduction performance of the thixotropic slurry while enhancing the fluidity of the slurry. The prepared slurry can quickly and fully fill the annular gap between the pipe and the surrounding soil, serving the functions of lubricating drag reduction and supporting the upper soil mass.

[0007] To achieve the above objective, the technical solution of the present invention is as follows:

[0008] In the first aspect, a pipe-jacking thixotropic slurry is prepared from raw materials in the following mass percentages:

[0009] Bentonite 6 - 10%, soda ash 0.2 - 1.2%, sodium carboxymethyl cellulose (CMC) 0.3 - 0.7%, fly ash microspheres 1% - 3%, potassium humate 0.5% - 1.5%, and glass fibers 0.4% - 0.8%, with the balance being water.

[0010] In the second aspect, a preparation method for the above pipe-jacking thixotropic slurry includes the following steps:

[0011] S1. Mix and stir bentonite with a set amount of water to obtain a first mixture.

[0012] S2. Mix and stir soda ash, sodium carboxymethyl cellulose, fly ash microspheres, potassium humate, and glass fibers with the remaining water to obtain a second mixture.

[0013] S3. Mix and stir the first mixture and the second mixture, and let it stand for 20 - 24 h.

[0014] In the third aspect, the application of the above pipe-jacking thixotropic slurry in pipe-jacking projects.

[0015] The beneficial effects of the present invention are as follows:

[0016] In view of the technical problems existing in the engineering application of thixotropic slurry, glass fiber and potassium humate are innovatively introduced in the present invention to achieve the synergistic optimization of the slurry performance. Under the construction conditions of thixotropic slurry, the water in the slurry will penetrate into the soil under the action of pressure. The fly ash microspheres added in the present invention can fill the gaps between soil particles in poor strata such as sand layers and pebble layers, improve the formation density, and play a role in stabilizing the formation. In addition, the fly ash microspheres form a discrete type of roller structure in the slurry, changing the sliding friction between the pipe wall and the soil body during pipe jacking construction into rolling friction, and reducing the side friction resistance during pipe jacking construction. Since the fly ash microspheres are hollow spheres, they are easily broken under high pressure or shear action and lose their mechanical properties. The glass fiber added in this application can be three-dimensionally distributed in the slurry to form a glass fiber network. As a rigid skeleton structure, the glass fiber significantly improves the support strength of the slurry through stress dispersion and bridging effects, thus making up for the deficiency of the fly ash microspheres in mechanical properties. On the other hand, after the fly ash microspheres are added to the thixotropic slurry, the apparent viscosity of the slurry increases and the fluidity becomes worse due to the adsorption of a part of water, which is not conducive to reaching positions far from the grouting hole. As an environmentally friendly viscosity reducer, potassium humate reduces the apparent viscosity of the slurry while not increasing the water loss rate of the thixotropic slurry, making the slurry better pumpable, and at the same time enhancing the stability of the slurry structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings forming a part of this specification are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention.

[0018] Figure 1 It is a schematic diagram of the preparation process in the specific embodiment of the present invention.

[0019] Figure 2 It is a statistical chart of the test results of the water loss in the specific embodiment of the present invention.

[0020] Figure 3 It is a statistical chart of the test results of the apparent viscosity in the specific embodiment of the present invention.

[0021] Figure 4 It is a diagram of the test device for the drag reduction performance in the specific embodiment of the present invention. SPECIFIC EMBODIMENTS

[0022] A typical embodiment of the present invention provides a pipe jacking thixotropic slurry, which is prepared from the following raw materials in mass percentages:

[0023] Bentonite 6-10%, soda ash 0.2-1.2%, sodium carboxymethyl cellulose (CMC) 0.3-0.7%, fly ash microspheres 1%-3%, potassium humate 0.5%-1.5% and glass fiber 0.4%-0.8%, and the balance is water.

[0024] Among the above raw materials, fly ash microspheres can reduce the side friction resistance during pipe jacking construction. However, their hollow structure is prone to fragmentation and loss of mechanical properties under high pressure or shear forces, and it also deteriorates the fluidity of the slurry. Glass fibers can form a rigid framework to enhance the support strength of the slurry, and potassium humate can significantly reduce the apparent viscosity of the slurry. Among the basic components of the thixotropic slurry, they can achieve the synergistic optimization of the slurry performance.

[0025] Optionally, the bentonite is sodium-based bentonite with high water absorption and large swelling ratio, and its main component is montmorillonite, meeting the requirements of GB / T20973-2020.

[0026] Optionally, the soda ash is Class I sodium carbonate, meeting the requirements of GB / T 210-2022. Its main function in the slurry mixing process is as a dispersant, promoting the binding ability between the solid and liquid phases in the slurry and increasing the slurry stability.

[0027] Optionally, the fly ash microspheres are light floating beads with a mesh size of 40 - 80 meshes and a hollow structure.

[0028] Optionally, the potassium humate, with a CAS number of 68514-28-3, is an environmentally friendly viscosity reducer that can adsorb heavy metal elements in the soil and has no adverse impact on the environment.

[0029] Optionally, the chopped glass fibers use conventional industrial-grade raw materials, with an average length of 3 mm, and a single filament diameter of several to dozens of micrometers, having a significant cost advantage.

[0030] Optionally, the pH of the water is 6.5 - 8.5.

[0031] A typical embodiment of the present invention provides the above-mentioned method for preparing the pipe jacking thixotropic slurry, including the following steps:

[0032] S1. Mix and stir the bentonite with a set amount of water (accounting for 80% - 90% of the total water volume) to obtain a first mixture;

[0033] S2. Mix and stir the soda ash, carboxymethyl cellulose sodium, fly ash microspheres, potassium humate, and glass fibers with the remaining water to obtain a second mixture;

[0034] S3. Slowly add the second mixture to the first mixture and mix, continuously stir until uniform, and let it stand for 20 - 24 h.

[0035] In the preparation method, the bentonite needs to be mixed with water first, and after sufficient hydration, the admixtures are added. Otherwise, it will affect the colloidal stability.

[0036] Optionally, in S1, the stirring speed is 400 - 600 r / min, and stir until there are no lumps in the first mixture.

[0037] Optionally, in S2, the stirring speed is 280 - 360 r / min; first mix soda ash, CMC, and glass fiber with water, then add fly ash microbeads and potassium humate, and continuously stir until uniform.

[0038] Optionally, in S3, the static environment temperature is 20 - 25 °C; the function of static placement is to fully expand the bentonite in the slurry.

[0039] A typical embodiment of the present invention provides the application of the above-mentioned pipe jacking thixotropic slurry in pipe jacking projects.

[0040] The pipe jacking thixotropic slurry is filled in the over-excavated area between the pipe jacking cutter head and the pipe wall by grouting, reducing the friction between the outer wall of the pipe jacking and the soil layer during jacking, and playing a role in supporting the upper soil and inhibiting soil settlement when jacking stops; among them, the over-excavated area is also called the over-excavation gap or annular void, which refers to the annular space formed when the actual cutting soil range of the pipe jacking machine cutter head is slightly larger than the pipe outer diameter during tunneling. The existence of this area is a common phenomenon in pipe jacking construction, and its design, control, and management are crucial for construction safety and formation stability.

[0041] Example 1

[0042] The pipe jacking thixotropic slurry includes the following components by mass fraction: bentonite 6%, soda ash 0.8%, sodium carboxymethyl cellulose (CMC) 0.5%, fly ash microbeads 1% - 3%, potassium humate 0.5% - 1.5%, and glass fiber 0.4% - 0.8%, with the balance being water; among them, fly ash microbeads, potassium humate, and glass fiber take multiple values within the set range as different experimental groups. The bentonite is sodium-based bentonite, mainly composed of montmorillonite, meeting the requirements of GB / T20973 - 2020; the soda ash is sodium carbonate type I, meeting the requirements of GB / T 210 - 2022; the fly ash microbeads are light floating beads with a mesh size of 40 - 80 meshes; the glass fiber is short-cut glass fiber with an average length of 3 mm.

[0043] In each experimental group, fly ash microbeads, potassium humate, and glass fiber are added according to the requirements of the orthogonal experiment, and the addition percentages of each experimental group are shown in Table 1. Among them, experimental group 1 is the basic thixotropic slurry, serving as a control.

[0044] Table 1

[0045]

[0046] The preparation method is as Figure 1 shown, including the steps:

[0047] S1. Mix bentonite with 80% of the total water volume and stir at a speed of 600 r / min until no lumps remain, obtaining the first mixture;

[0048] S2. Mix soda ash, sodium carboxymethyl cellulose, fly ash microspheres, potassium humate, and glass fiber with the remaining water and stir evenly at a speed of 300 r / min, obtaining the second mixture;

[0049] S3. Mix the first mixture and the second mixture evenly, and then let it stand in an environment of 23 ± 2 °C for 20 - 24 h.

[0050] The detection contents include the 24-hour water separation rate, apparent viscosity, water loss, and drag reduction performance of each experimental group.

[0051] The 24-hour water separation rate is measured by the ratio of the volume of water separated from the slurry after standing in a 1000 mL stoppered graduated cylinder for 24 h to the original slurry volume; the apparent viscosity is measured using a six-speed rotational viscometer, and the apparent viscosity is 1 / 2 of the reading on the 600 rpm scale; the water loss is measured using a medium-pressure filter press. Inject the slurry into the slurry cylinder, keep the pressure in the cylinder at 0.69 MPa, and the water separated under the fixed pressure drips into a 25 mL graduated cylinder. After timing for 30 min, relieve the pressure, remove the slurry cylinder, and observe the volume of water in the graduated cylinder.

[0052] The 24-hour water separation rate refers to the volume percentage of water separated from the slurry due to gravity, which can characterize the water retention performance of the pipe jacking thixotropic slurry.

[0053] The apparent viscosity refers to the flow resistance exhibited by the slurry at a specific shear rate (such as 600 rpm), with the unit of mPa·s (millipascal second); it comprehensively reflects the fluidity, slag-carrying capacity, and shear dilution characteristics of the slurry, and can characterize the flow performance of the pipe jacking thixotropic slurry.

[0054] The water loss refers to the volume of solution filtered out by a certain volume of slurry under a pressure of 0.69 MPa within a specified time; it reflects the sealing performance and formation protection ability of the slurry, and is one of the core indicators for evaluating the slurry performance, which can characterize the anti-filtration loss performance and stability ability of the pipe jacking thixotropic slurry.

[0055] The test results are shown in Table 2.

[0056] Table 2

[0057]

[0058]

[0059] Process the data to obtain the statistical chart of the test results of the water loss as shown in Figure 2 and as shown in Figure 3Statistical graph of the test results of the apparent viscosity shown

[0060] It can be seen that by comparing the thixotropic mud properties of the basic thixotropic mud and the modified experimental group, the 24-hour water separation rate of the thixotropic mud in other experimental groups has decreased significantly, indicating that the stability of the thixotropic mud in the modified experimental group is better than that of the basic thixotropic mud. When standing still or under a certain external force, water is not easily separated from the mud. The water loss in 30 minutes shows an overall downward trend with the increase of the mass fraction of fly ash microspheres. From experimental groups 2, 3, and 4, it can be seen that at the same mass fraction of fly ash microspheres, with the increase of the mass fraction of glass fiber, the water loss of the mud gradually decreases. The maximum water loss can be reduced to 62.5% of the water loss of the basic thixotropic mud, indicating that the filtration ability of the modified mud has been significantly improved. Under a certain grouting pressure, water is not easily separated from the mud, the mud is more stable, the formed mud cake is denser, and the supporting effect is also better than that of the basic thixotropic mud. The mud jacket formed by the mud can play a role in inhibiting the collapse and deformation of the soil body. The incorporation of potassium humate significantly improves the rheological properties of the mud system. Comparing experimental group 1 with experimental groups 2 - 10, the apparent viscosity of the mud after adding potassium humate is less than that of the basic mud, but the water loss does not increase with the decrease of the apparent viscosity. This indicates that the introduction of potassium humate not only optimizes the rheological characteristics of the mud but also enhances the stability of the mud structure. The apparent viscosity reflects the fluidity of the mud. The mud prepared by the method for preparing the pipe jacking thixotropic mud proposed in the present invention has an apparent viscosity much lower than that of the basic thixotropic mud. The mud can quickly and fully fill the annular gap between the pipe and the surrounding soil body. And when supplementary mud is injected later, the mud with good fluidity can also quickly adapt to and fill the gap, providing lubrication and support for the pipe jacking.

[0061] The change relationship between the water loss of the mud and the content of fly ash microspheres and glass fiber is more significant. According to experimental groups 2 - 4, 5 - 7, and 8 - 10, with the increase of the mass fraction of fly ash microspheres, although the water loss fluctuates, it shows an overall downward trend. According to experimental groups 2 - 4, at the same incorporation amount of fly ash microspheres, the greater the content of glass fiber, the lower the water loss. This shows that both fly ash microspheres and glass fiber improve the filtration performance of the mud. Fly ash microspheres have a large specific surface area and can adsorb a large amount of free water. Glass fiber is easy to form hydrogen bonds with polymers in the mud to produce an interfacial adsorption layer. Combining the material characteristics analysis of fly ash microspheres and glass fiber, fly ash microspheres are hollow spheres and will lose their mechanical properties when subjected to greater pressure or shear force. The addition of glass fiber forms a three-dimensional distributed glass fiber network to form a rigid skeleton structure, which significantly improves the support strength of the mud through stress dispersion and bridging effects, making up for the deficiencies after adding fly ash microspheres to the thixotropic mud.

[0062] The relationship between the flow properties of the slurry and the changes in the content of fly ash microspheres and potassium humate is more significant. Comparing test groups 2-4, 5-7, and 8-10, as the content of fly ash microspheres increases, the apparent viscosity of the slurry shows a slight upward trend. This is because its porous vitreous structure and surface activity will adsorb some moisture, promoting an increase in viscosity. However, after adding potassium humate to test groups 2-10, the apparent viscosity of the slurry is lower than that of the basic slurry (test group 1) used as a control, indicating that potassium humate has a significant effect on improving the fluidity of the slurry and offsets and exceeds the viscosity-increasing effect of fly ash microspheres.

[0063] During the measurement of the drag reduction performance, use a device as Figure 4 shown. The method includes: injecting the slurry of the test group to be tested between a concrete block (weighing 0.491 kg) made of the same material as the pipe jacking segment and the soil body (the type of soil body can be changed according to specific construction conditions), and using a motor to pull the block at a constant speed to simulate the pipe jacking process. Measure the average pulling force of the block in the slurry state after injecting the slurry. The pulling force f 平均 is shown by a spring dynamometer, and calculate the friction coefficient μ after injecting different slurries (μ = f 平均 / mg, friction coefficient = average pulling force in the drag reduction state / gravity of the concrete block). The results are shown in Table 3.

[0064] Table 3

[0065]

[0066]

[0067] Comparing test group 1 with test groups 2-10, the interfacial friction coefficient of the thixotropic slurry compound-modified by fly ash microspheres and glass fibers is significantly reduced from 0.49 in the reference group to 0.25-0.44 (a decrease of 10%-49%). This shows that the drag reduction ability of the thixotropic slurry prepared by the present invention has been significantly improved. The fly ash microspheres build a "particle bearing" effect at the contact interface between the pipe jacking wall and the soil body. Based on the tribological theory analysis, the friction mode of the contact surface has changed fundamentally, from sliding friction to rolling friction. After adding glass fibers, the axially arranged fiber bundles form an orbital guiding effect, restricting the disorder of the rollers under the action of shear force, and further increasing the drag reduction performance of the thixotropic slurry.

[0068] The thixotropic slurry provided by the present invention should have the characteristics of high drag reduction, strong support, low water loss, stable slurry performance, low raw material cost and environmental friendliness; it does not rely on components such as xanthan gum to improve water retention, and can maintain the support effect and drag reduction effect under high pressure or shear action, with good fluidity; during actual construction, the grouting pressure (0.1 - 0.3 MPa) can be maintained within a small range, enabling the slurry to easily form a complete slurry sleeve on the pipe wall, avoiding the problems of increasing the side friction resistance of the pipe jacking and the degree of ground disturbance caused by excessive grouting pressure; and also avoiding the damage to the structure of hollow microspheres caused by the high pressure or shear action resulting from excessive grouting pressure, and enabling the fly ash microspheres to maintain a complete structural state under a small grouting pressure to effectively achieve the drag reduction effect.

[0069] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention can have various modifications and changes. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.

Claims

1. A pipe jacking thixotropic slurry, characterized in that, Prepared from raw materials with the following mass percentages: Bentonite 6-10%, soda ash 0.2-1.2%, sodium carboxymethyl cellulose 0.3-0.7%, fly ash microspheres 1%-3%, potassium humate 0.5%-1.5% and glass fiber 0.4%-0.8%, the balance being water.

2. The pipe jacking thixotropic slurry according to claim 1, wherein The bentonite is sodium-based bentonite, and its composition includes montmorillonite.

3. The thixotropic slurry for pipe jacking according to claim 1, wherein The soda ash is Class I sodium carbonate.

4. The pipe jacking thixotropic slurry according to claim 1, wherein, The fly ash microspheres are lightweight floating beads with a mesh size of 40-80 meshes.

5. The thixotropic slurry for pipe jacking according to claim 1, characterized in that The glass fiber is chopped glass fiber with an average length of 3 mm.

6. A preparation method of the jacking pipe thixotropic slurry according to any one of claims 1-5, characterized in that, Including the following steps: S1. Mix and stir the bentonite with a set amount of water to obtain a first mixture; S2. Mix and stir the soda ash, sodium carboxymethyl cellulose, fly ash microspheres, potassium humate and glass fiber with the remaining water to obtain a second mixture; S3. Mix and stir the first mixture and the second mixture, and let it stand for 20-24 h.

7. The preparation method of the pipe jacking thixotropic slurry according to claim 6, characterized in that, In S1, the stirring speed is 400-600 r / min, and stir until there is no agglomeration in the first mixture.

8. The preparation method of the jacking pipe thixotropic slurry according to claim 6, characterized in that, In S2, the stirring speed is 280-360 r / min.

9. The preparation method of the pipe jacking thixotropic slurry according to claim 6, characterized in that, In S3, the ambient temperature for standing is 20-25 °C.

10. Application of a pipe jacking thixotropic slurry as described in any one of claims 1-5 in a pipe jacking project.

Citation Information

Cited By

  • Thixotropic slurry suitable for circular pipe jacking construction in pebble stratum and preparation method of thixotropic slurry

    CN120737822A